MAPPING ANALYSIS OF VOCATIONAL HIGH SCHOOL MODEL BASED ON REGIONAL EXCELLENCE BONE BOLANGO REGENCY IN THE TOMINI BAY REGION - BUYUNG RAHMAT MACHMOED; PURNAMAWATI; HASANAH NUR (Pascasarjana Universitas Negeri Makassar, 2023)
This study aims to analyze the mapping of vocational high school models based on regional superior potential and community needs of Bone Bolango Regency, in the Tomini Bay Region. The research method used is a combination of the Sequential Explanatory model with Location Quotient (LQ) data analysis and qualitative data analysis. The results of the study are the mapping of regional leading sectors with 9 basic sectors, namely, mining and quarrying, processing industry, construction, wholesale and retail trade, car and motorcycle repair, real estate, company services, government administration, education services, health services and social activities. The largest LQ value of the 9 sectors is the Processing Industry sector, with an LQ value of 1.507. There are 7 SMK competencies in Bone Bolango Regency, 2 of which are directly adjacent to the Tomini Bay region. There are 2 (two) skill competencies that need to be removed or replaced, namely, Network Computer Engineering and Visual Communication Design. 7 Expertise competencies that can be developed based on the analysis of potential leading sectors are: 1 Agribusiness of Food Crops and Horticulture, 2 Agribusiness of Poultry, 3 Agribusiness of Agricultural Product Processing, 4 Nautical Fishing Vessels, 5 Agribusiness of Freshwater Fisheries, 6 Agribusiness of Fishery Product Processing, 7 Nursing Assistant.